Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMPN 3 Pariaman - SUCI JUANDIKA (Departemen Matematika, 2019)
Mathematical communication ability is one of the purpose in mathematics learning. Every students must have a good mathematical communication ability. But infact, mathematical communication ability of students at second grade SMPN 3 Pariaman is not optimal. It is caused by learning model that used has not facilitated students to develop their mathematical communication ability. One effort to overcome this problem is by applying Think Talk Write of Cooperative Learning in mathematics learning. This learning model helps students to develop their mathematical communication ability. The type of research is a quasi-experimental design with Static Group Design. The research hypothesis is carried out by using the t-test. Based on the results of data analysis, it was concluded that mathematical communication ability of students who learn with the cooperative learning model of Think Talk Write type are better than the mathematical communication ability of students who learn by direct learning. Keywords – Mathematical Communication Ability, ThinkxTalk Write, Direct Learning